Reconstructing Islamic Social Education through Zakat Paradigm: Insights from Tafsir Al-Qur’an Al-Majid An-Nur - Salim, Agus; Hanum OK, Azizah (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study proposes a reconstruction of Islamic social education by re-evaluating the concept of Zakat through the lens of Tafsir Al-Qur’an Al-Majid An-Nur by Hasbi Ash-Shiddieqy. While Zakat is traditionally taught as a static pillar of jurisprudence (fiqh), this research identifies a critical pedagogical gap: its potential as a catalyst for social transformation remains underutilised. Employing a qualitative library research methodology, the study performs a thematic excavation of Zakat-related exegesis in Ash-Shiddieqy’s work, synthesising classical interpretations with modern social education theories. The findings reveal a “Qur’anic Sunnah” that inextricably links prayer (Salah) to Zakat, forming a dual mission of individual spiritual growth and collective societal improvement. Ash-Shiddieqy’s exegesis presents Zakat as a sophisticated instrument of thaharah (purification) across three dimensions: wealth, the soul, and the community. Furthermore, the study highlights an educational “shock therapy” in the text, in which the enforcement of Zakat, symbolised by the historical precedent of the first Caliphate, establishes an absolute social contract that transcends individual property rights. By expanding the interpretation of the eight asnaf (beneficiaries) into a framework for sustainable community development, this research offers a novel social-educational paradigm. The study concludes that reconstructing Islamic education through the Zakat concept shifts the pedagogical focus from passive ritualism to active orthopraxis, providing a humanistic framework essential for addressing contemporary moral crises and achieving structural social justice.